Effect of SGLT2-Inhibitors on Epicardial Adipose Tissue: A Meta-Analysis - Masson, Walter (2021)
(1) Sodium–glucose cotransporter-2 inhibitors (SGLT2-i) reduce adipose tissue and cardiovascular events in patients with type 2 diabetes (T2D). Accumulation of epicardial adipose tissue (EAT) is associated with increased cardio-metabolic risks and obstructive coronary disease events in patients with T2D. (2) We performed a systematic review and meta-analysis of SGLT2-i therapy on T2D patients, reporting data on changes in EAT after searching the PubMed/MEDLINE, Embase, Science Direct, Scopus, Google Scholar, and Cochrane databases. A random effects or fixed effects model meta-analysis was then applied. (3) Results: A total of three studies (n = 64 patients with SGLT2-i, n = 62 with standard therapy) were included in the final analysis. SGLT2 inhibitors reduced EAT (SMD: −0.82 (−1.49; −0.15); p < 0.0001). An exploratory analysis showed that HbA1c was significantly reduced with SGLT2-i use, while body mass index was not significantly reduced with this drug. (4) Conclusions: This meta-analysis suggests that the amount of EAT is significantly reduced in T2D patients with SGLT2-i treatment.